Summary of Baseline Household Survey Results: Bagerhat, Bangladesh - Bangladesh Centre for Advanced Studies (2013)
The results from the baseline survey show that almost all households produce small livestock and livestock products and approximately two-thirds of households produce food crops. More than half produce fish and nearly half produce vegetables. Most of the households producing these products also consume them, with a smaller proportion selling such products. Almost all households also consume food crops and fruit from off-farm sources. Both men and women take responsibility for on-farm work, while men complete 95% of the agricultural workload off-farm. The three most important crops in Bagerhat were reported to be rice, leafy vegetables and potatoes. Nearly three-quarters of households reported using fertilizers in the past 12 months. There is a wide range of food security situations in Bagerhat. Forty percent of households reported being food secure all year round, while a fifth of households reported more than 6 hungry months per year.